Numerical Simulation of Driven Convective Heat Transfer Based Lattice Boltzmann Method in a Porous Cavity - You-Sheng Xu; Rui-Min Wang; Guo-Neng Li; You-Qu Zheng (Journal of Chemistry)
A lattice Boltzmann model of the uniform velocity, driven convective thermal conductivity in a porous cavity is studied. The Darcy, Richardson, and Reynolds numbers are shown to have a significant influence on the heat transfer behavior and the horizontal velocity of the flow field, while the porosity has little influence on either. The model is validated by the average Nusselt number at different Reynolds numbers, and the numerical results are in good agreement with available published data.